Dilemma in Diagnosis of Parotid Gland Swelling: A Case Report of Pilomatrix Carcinoma Involving Parotid Gland (Medical Forum Monthly, 2022)
Pilomatrix carcinoma mostly occurs in the head & neck region and upper and lower extremities are also known sites of pilomatrix carcinoma. It is usually misdiagnosed as other benign tumors and leads to inadequate treatment planning which eventually results in recurrence as in our case. We present this case due to its relative rarity, to raise awareness about its clinical features, diagnosis and treatment. A male patients with age 27 years old presented to our OPD with complains of recurrent swelling in right infra auricular region. It was diagnosed as keratinizing squamous cell carcinoma. Primarily diagnosed with the help of FNAC, CT scan and finally with excisional biopsy of the mass.